Resistance to thyroid hormone accompanied by atrial fibrillation. (1st October 2018) - Sato, Haruhiro; Tomita, Yuichiro
Summary: Resistance to thyroid hormone (RTH), which is primarily caused by mutations in the thyroid hormone (TH) receptor beta ( THRB ) gene, is dominantly inherited syndrome of variable tissue hyposensitivity to TH. We herein describe a case involving a 22-year-old Japanese man with RTH and atrial fibrillation (AF) complaining of palpitation and general fatigue. Electrocardiography results revealed AF. He exhibited elevated TH levels and an inappropriately normal level of thyroid-stimulating hormone (TSH). Despite being negative for anti-TSH receptor antibody, thyroid-stimulating antibody and anti-thyroperoxidase antibody, the patient was positive for anti-thyroglobulin (Tg) antibody. Genetic analysis of the THRB gene identified a missense mutation, F269L, leading to the diagnosis of RTH. Normal sinus rhythm was achieved after 1 week of oral bisoprolol fumarate (5 mg/day) administration. After 3 years on bisoprolol fumarate, the patient had been doing well with normal sinus rhythm, syndrome of inappropriate secretion of TSH (SITSH) and positive titer of anti-Tg antibody. Learning points: Atrial fibrillation can occur in patients with RTH. Only a few cases have been reported on the coexistence of RTH and atrial fibrillation. No consensus exists regarding the management of atrial fibrillation in patients with RTH. Administration of bisoprolol fumarate, a beta-blocker, can ameliorate atrial fibrillation in RTH.